Stukostrachy - King, Stephen, 1947-; Praski, Lukasz (Warszawa : Proszynski i S-ka, 2003)
Polish translation of "Tommyknockers". A woman in a small New England town stumbles across a strange object buried behind her house and releases a long sleeping ancient evil.
Keywords: Good and evil -- Fiction; Maine -- Fiction